Activist Discourse and the Origins of Feminist Shakespeare Studies - Nerio, Magdalena (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
This essay reconsiders interpretations of Shakespeare by Irish writer Anna Murphy Jameson and the American Transcendentalist Margaret Fuller. Developing an informal method in which the voice of the female critic rallies in defence of Shakespeare’s heroines, they intervene in a male-dominated intellectual sphere to model alternative forms of women’s learning that take root outside of formalized institutional channels. Jameson, in Shakespeare’s Heroines, invokes the language of authentic Romantic selfhood and artistic freedom, recovering Shakespeare’s female characters from earlier critical aspersion as figures of exceptional female eloquence and resilience; she adopts a conversational critical voice to involve her female readers in the interpretative process itself. Fuller, in Woman in Nineteenth Century, speaks authoritatively as a kind of female prophet to argue that women’s creative reinterpretations of Shakespeare point the way to a revitalization of a sterile literary critical field. Both writers call for the reform of women’s education through revisionist interpretations of history attuned to the representation of female exceptionalism. In embryonic form, these nineteenth century feminist writings formulate a persistent strain of socially engaged, activist feminist criticism of Shakespeare.